Soft-Tissue Sarcoma following Traumatic Injury: Case Report and Review of the Literature - Bar, Yael; Merimsky, Ofer (Frontiers in Oncology, 2017)
Soft-tissue sarcomas are a heterogeneous group of tumors, which accounts for 1-2% of adult cancers worldwide. Despite quite a few reports on traumatic events followed by STS formation, the link between the two events remains a point of controversy. In this paper, we present the case of a young patient who had a Rhabdomyosarcoma in the lower extremity, which had developed in the same location where the patient was wounded by a gunshot nine years earlier. X-Ray and CT scans clearly showed metal fragments in the area of sarcoma formation. the patient underwent neoadjuvant chemotherapy treatment, to which the tumor was, unfortunately, unresponsive. Therefore, the patient was referred to below-knee amputation of the injured leg. There are several possible etiological factors for sarcoma development in this patient, including tissue damage and inflammation, as well as the presence of metal fragments in the tissue and the limb’s exposure to radiation during multiple imaging tests. Here, we will discuss the potential influence wielded by the injury itself, as well as its complications and its medical management on the formation of the sarcoma, in light of the current literature.